Selective oxidation of methane to methanol and methyl hydroperoxide over palladium modified MoO3 photocatalyst under ambient conditions. Issue 11 (6th May 2022) - Sun, Songmei; Dummer, Nicholas F.; Bere, Takudzwa; Barnes, Alexandra J.; Shaw, Greg; Douthwaite, Mark; Pattisson, Samuel; Lewis, Richard J.; Richards, Nia; Morgan, David J.; Hutchings, Graham J.
Abstract : In situ generated H2 O2 from water on Pd–MoO3 catalyst can oxide methane into methanol and methyl hydroperoxide with high selectivity under simulated solar light irradiation. Abstract : Selective partial oxidation of methane to valuable oxygenated products remains a great challenge, as typically over oxidation of oxygenated products to CO x is observed. Weak oxidative species on the catalyst surface have a great potential to overcome this limitation. However, weak oxidative species usually have low concentrations and are easily decomposed. Here we report a Pd/MoO3 photocatalyst which can realize excellent methane oxidation to methanol and methyl hydroperoxide in pure water, under simulated solar light by in situ generated H2 O2 at room temperature and pressure. The combined selectivity for methanol and methyl hydroperoxide is up to 98.6%, representing a productivity rate of 42.5 μmol gcat −1 h −1 . Further studies on the reaction mechanism indicate that PdO species on the Pd loaded MoO3 catalyst play an essential role in the suppression of over oxidation. In this case PdO traps the photo-generated electrons, leaving photo-generated holes for decomposition of H2 O2 into weak oxidative hydroperoxyl radicals which are not involved in the formation of over oxidation products.